Parental Knowledge and Motivation in HPV Vaccination Decision-Making for Cervical Cancer Prevention Among Children - Elin Ermi Eliani; Riska Hediya Putri; Surmiasih; Rini Palupi (Viva Medika, 2026)
Cervical cancer remains one of the leading causes of mortality among women in Indonesia, with persistent challenges in preventive efforts. Vaccination against the Human papillomavirus (HPV) is recognized as an effective primary prevention strategy to reduce the incidence of cervical cancer. However, HPV vaccination coverage among school-aged children in Indonesia remains suboptimal, partly due to limited parental awareness and varying levels of motivation. This study aimed to examine the relationship between parental knowledge of cervical cancer prevention and parental motivation toward HPV vaccination in children. A quantitative analytical study with a cross-sectional design was conducted among parents of female students in grades five and six at SD Negeri 5 Kresnomulyo, Pringsewu. A total of 67 respondents were recruited using a total sampling technique. Data were collected through validated questionnaires assessing knowledge and motivation levels and were analyzed using the Chi-square test. The findings demonstrated a statistically significant association between parental knowledge and motivation toward HPV vaccination (p < 0.001). These results suggest that improving parental knowledge through structured and targeted health education programs may strengthen motivation and increase acceptance of HPV vaccination as an essential preventive measure against cervical cancer